Identification of HMOX1 as a Critical Ferroptosis-Related Gene in Atherosclerosis - Wu, Daiqian; Hu, Qian; Wang, Yuqing; Jin, Mengying; Tao, Ziqi; Wan, Jing (Frontiers in Cardiovascular Medicine, 2022)
Ferroptosis is a novel form of programmed iron-dependent cell death. The ferroptosis-related genes (FRGs) have been recognized as biomarkers for cancers. Increasing evidence has indicated that ferroptosis is involved in the process of atherosclerosis. However, the potential FRGs used for the diagnosis, prognosis and therapy for atherosclerosis are still unclear. We aimed to identify the ferroptosis-related differentially expressed genes (DEGs) of atherosclerosis. We downloaded the mRNA-sequencing data of patients with atherosclerosis from the Gene Expression Omnibus (GEO) database. HMOX1 was identified as an essential ferroptosis-related DEG by bioinformatic analysis of the GSE28829 and GSE43292 datasets. The pro-ferroptotic effect of HMOX1 was validated through cell experiments. Then we conducted a single-gene analysis of HMOX1 and found that high-expression of HMOX1 in atherosclerotic plaques was accompanied by matrix metalloproteinases (MMPs) producing and M0 macrophages infiltration. Taken together, our present study suggested HMOX1 as a potential diagnostic biomarker for atherosclerosis and provided more evidence about the vital role of ferroptosis in atherosclerosis progression.